PENGARUH PEMBAWA ACARA INDONESIA LAWYERS CLUB SUKARNI ILYAS DI TV ONE TERHADAP MINAT MENONTON MAHASISWA UIN RADEN FATAH PALEMBANG (STUDI PADA MAHASISWA JURNALISTIK 2017) - Iqbal Pratama Laras Sakti; M Amin Sihabuddin; Emi Puspita Dewi (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the extent of the influence of “Sukarni Ilyas” Talkshow Indonesia Lawyer club against interest watch (Studies on students UIN Raden Fatah Palembang Jurnalism force in 2017). The population of this study of UIN Raden Fatah, the Faculty of Da’wah and communication Departement Jounalism as many as 91 students. The determination of the analyzed uses analysis based on the characteristics of respondents, namely based on gender and based on class. Based on gender in which sample obtained by (38,5 %) 35 male students and (61,5 %) 56 female students. Based on the class of A, B, C, and D played as if more students were in a D class I namely as many as 27 students were 29.7 % of respondents. This study in a quantitative study and assisted with the programs SPPS V 16 and data collection uses kusioner. kusioner that is covered, namely alternatives answers have been determined before researchers. Based on analysis of simple regressing obtained watching 0,814 (81%) which shows positive influence againts the host so if the presenter increased, the interest increased. Based on signifikasi parsial (test t) obtained a value of host shows (X) 0,5 < 0F 7.327> t-it 1.986 (7.327>1.986 and sig 0.50). Based on the coefficient of kolerasi obtained a value of R 0.613 meaning that the relationship (realtion) between the host of watching has a strong relationship of 61.3%. So that the results of this study showed that a particulary strong influence between hosts interest in watch UIN Raden Fatah, Faculty of Da’wah and communication depatement of Journalists 2017. Keywords: Quantitative researcher, infulene talkshow, Interest watching